The innovator's DNA : mastering the five skills of disruptive innovators - Dyer, Jeff (Harvard Business Press, 2011)
"How can I innovate? How do I spot people who are more likely to generate disruptive business ideas for my organization? How can I help my team be more innovative? If you've ever asked yourself these questions, then you know there is no silver bullet for learning how to be more innovative. Indeed, conventional wisdom says that some people naturally and habitually have that "spark" and other people just don't. Picking up where The Innovator's Solution leaves off, authors Jeff Dyer and Hal Gregersen offer a different view, and instead argue that all people can learn how to be more innovative. In The Innovator's DNA, the authors now show that you can train yourself -- and others -- to think and act more like an innovator, even like those high profile innovators such as Scott Cook, Mike Lazardis, Meg Whitman, and AG Lafley. In partnership with Clayton Christensen, Dyer and Gregersen launched an in-depth study of "innovative entrepreneurs"--That is, founders and CEOs of companies based on a unique value proposition relative to incumbents -- and compared them to other successful (but not innovative) CEOs and executives. Through in-depth interviews, 360 and survey data, Dyer, Gergersen, and Christensen identified a set of five "discovery skills" (associational thinking, questioning, observing, experimenting, and idea networking) that distinguish innovative entrepreneurs from typical executives. This book explains each of the discovery skills, how to develop them, and how to use them in combination to generate new ideas. It shows how to rate, and then build upon, your own "Innovator's DNA", using the same diagnostics used in their study of successful innovators"--Provided by publisher.